Relative age effect at Concacaf championships: Influence of sex, age, nationality, playing position, and playing status - Matthew Andrew; Sam Barraclough; James H. Dugdale; Matthew J. Reeves; Andrew O. Triggs; Adam L. Kelly (PLoS ONE, 2025)
Relative age effects in soccer are typified by an overrepresentation of players born earlier in the selection year. Examinations of relative age effects remain limited in female players and developing soccer nations. The aim of the present study was to examine the influence of sex, age, nation, playing position, and playing status in international level soccer players under Confederation of North, Central American and Caribbean Association Football (Concacaf). The sample consisted of a total of 1,959 active soccer players from 24 soccer nations that competed in recent Concacaf Championships. Results indicated an evident relative age effect in male [p < 0.05] but not female [p = 0.81] players. Male players were over‐represented by players born in the first quartile for the U17 [p < 0.01] level, however, this over‐representation did not transfer to the U20 or senior levels. No relative age effects were observed at any level for female players. A large proportion of nations demonstrated relative age effects in male, but not female samples. Relative age effects were shown for players participating at age group level, but not those ‘playing-up’. Results from this study highlight the continued disparity in relative age effects prevalence between male and female players raises further questions regarding the value of selecting relatively older players to metrics of success, transition, and selection for senior international soccer. This information can be used to advance talent identification and development in Concacaf nations.